Implementation and results of a gastrointestinal cancer screening program in an Amazon rainforest village: A descriptive study - Averbach, Pedro; Ferrari, Angelo Paulo; Toscano, Cristiana M; Borges, José Luiz; Averbach, Marcelo (Endoscopy International Open, 2021)
Background and study aims Gastrointestinal cancer is an important cause of death worldwide. Remote populations are especially vulnerable to these conditions due to reduced access to screening and adequate treatment. In this context, the Belterra project was designed as a pilot taskforce to deliver gastrointestinal screening to an underserved Amazonian population and to spread knowledge and practice to local health workers. This study aimed to describe the implementation and present the results of the Belterra Project.Patients and methods The project took place between October 2014 and December 2017 in Belterra, Pará, Brazil. Public-private partnerships were obtained and were essential for funding. The project required complex logistic solutions to provide gastrointestinal screening to every inhabitant between 50 and 70 years of age, including medical equipment and personal transportation to a remote area. Subjects were asked about their medical history, and received a physical examination, endoscopic examinations, and stool tests.Results Over the course of 19 expeditions, we screened 2,022 inhabitants of Belterra, aged 50 to 70 years. Five colorectal and six gastric adenocarcinomas were diagnosed, as were several lower-stage lesions. Overall, 26 % of the participants undergoing colonoscopy showed some type of colonic lesion.Conclusions Notwithstanding the geographical, cultural, and financial barriers, this study suggests that the implementation of a gastrointestinal cancer screening program for remote Brazilian populations is feasible, reaching high adherence. Although logistics is very demanding, such campaigns may be a good strategy to provide mass gastrointestinal cancer screening for underserved populations.